2006
DOI: 10.1007/s00192-006-0262-z
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the prolapsed uterus is a valid option: medium term results of a prospective comparative study with the posterior intravaginal slingoplasty operation

Abstract: It has been reported that, by the age of 80, the risk of women to undergo surgery for the treatment of pelvic organ prolapse (POP) exceeds 10%, a percentage expected to increase with the rise in life expectancy. The vaginal approach for POP reconstructive operations is associated with fewer complications and results in a shorter rehabilitation period than the abdominal route, whereas hysterectomy is widely performed concomitantly whenever the uterus is significantly prolapsed. However, there is no clear eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 31 publications
0
36
0
2
Order By: Relevance
“…However, as with the majority of studies reported in this review, well-designed studies with clear outcomes (both anatomical and functional) on the IVS posterior procedure have to be awaited. Removal of the uterus during the procedure did not alter the erosion rate but it did increase the hospital admission time (1.5 versus 4.2 days, P=0.002) [37].…”
Section: Surgical Proceduresmentioning
confidence: 88%
See 3 more Smart Citations
“…However, as with the majority of studies reported in this review, well-designed studies with clear outcomes (both anatomical and functional) on the IVS posterior procedure have to be awaited. Removal of the uterus during the procedure did not alter the erosion rate but it did increase the hospital admission time (1.5 versus 4.2 days, P=0.002) [37].…”
Section: Surgical Proceduresmentioning
confidence: 88%
“…After assessment of the 32 reports and their reference lists, only four studies describing posterior intravaginal slingplasty in women preserving their uterus were available [37][38][39][40]. Because Mattox et al did not describe their subgroup of only two women with preservation of the uterus separately (21 women without a uterus), this report was excluded from the analyses of anatomical and functional outcomes [40].…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…A extrusão da tela ocorreu em 13,6% no grupo histerectomizado versus 11,4% no grupo de preservação uterina. Os autores concluíram que a correção do prolapso uterino com tela sintética é eficaz e segura 17 . Pelo exposto, justifica-se a necessidade do desenvolvimento de técnicas cirúrgicas menos invasivas, que preservem a anatomia e as funções do assoalho pélvico feminino, o que estimulou o desenvolvimento deste estudo, que objetiva comparar os resultados anatômicos pós-operatórios de pacientes portadoras de prolapso uterino tratadas por meio de tela de polipropileno para correção do defeito apical, comparando histerectomia vaginal (HV) com a histeropexia(HP).…”
Section: Descritoresunclassified